2015
DOI: 10.1103/physreve.92.062827
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic theory of traffic-flow instability governing traffic breakdown at highway bottlenecks: Growing wave of increase in speed in synchronized flow

Abstract: We have revealed a growing local speed wave of increase in speed that can randomly occur in synchronized flow (S) at a highway bottleneck. The development of such a traffic flow instability leads to free flow (F) at the bottleneck; therefore, we call this instability as an S→F instability. Whereas the S→F instability leads to a local increase in speed (growing acceleration wave), in contrast, the classical traffic flow instability introduced in 50s-60s and incorporated later in a huge number of traffic flow mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 114 publications
6
44
0
Order By: Relevance
“…In accordance with the three‐phase theory, Kerner's S→F instability should govern traffic breakdown (F→S transition) at freeway bottlenecks [27]. In the theory of the S→F instability it has also been found that before the traffic breakdown (F→S transition) occurs with the resulting congested pattern formation, there can be a series of random F→S transitions that are all followed by S→F transitions caused by the S→F instability.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…In accordance with the three‐phase theory, Kerner's S→F instability should govern traffic breakdown (F→S transition) at freeway bottlenecks [27]. In the theory of the S→F instability it has also been found that before the traffic breakdown (F→S transition) occurs with the resulting congested pattern formation, there can be a series of random F→S transitions that are all followed by S→F transitions caused by the S→F instability.…”
Section: Introductionmentioning
confidence: 79%
“…Simulations of classic traffic flow instability of Herman et al [9] and Gazis et al [10] in free flow in a traffic flow model (a) GM model class (b, c) S→F instability in synchronised flow introduced in Kerner's three‐phase theory (adapted from [27])…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is statement is related to the phenomenon observed in Section 1. However, unfortunately, in Kerner's abovementioned and following works [4][5][6], clear de nition of HNAC and explicit formulas were not provided, either in other followers' works [7,8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In D€ ulgar et al 2019, the authors were motivated by the lack of empirical characterization of traffic "breakdown" as a two-way transition between different traffic states. The authors adopt the classification of Kerner (2015) that divides the traffic fundamental diagram into three regions. The traffic breakdown is then seen as a transition between a Free-flow Region (designated by F) and a Synchronized Region (designated by S): the "nucleation" in the F-S transition leads to a traffic breakdown that is governed in its turn by the S-F "instability."…”
Section: Recent Advances In Traffic Flow Modeling and Detectionmentioning
confidence: 99%